Analisis Perbandingan Kinerja Keuangan Pada Perusahaan Air Minum Dalam Kemasan (AMDK) Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2020-2024 - Ismi Dwi Ardini (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This study compares the financial performance of three bottled drinking water (BDW) companies listed on the Indonesia Stock Exchange, namely PT Mayora Indah Tbk (MYOR), PT Sariguna Primatirta Tbk (CLEO), and PT Akasha Wira International Tbk (ADES) during the 2020–2024 period. Data were obtained from annual financial reports and analyzed using liquidity, solvency, activity, and profitability ratios. The results show that ADES has the most stable liquidity, MYOR remains adequate though fluctuating, while CLEO shows an improving trend. CLEO records the highest solvency risk, MYOR maintains a healthy capital structure, and ADES shows improvement despite an increase in DER. In terms of activity, CLEO is the most efficient in asset turnover. Regarding profitability, CLEO and ADES are more efficient in managing earnings compared to MYOR.